IDAROH MAHARATUL LUGHAH AL-ARABIYAH BISYU'BATI TADRIS AL-LUGHAH AL-ARABIYAHI KULIYAH AT-TARBIYAH AL-WAL MUDARRISIYAH JAMI'AH MATARAM AL-ISLAMIYAH AL-HUKUMIYAH - Raudatussolihah, Baiq; Rahman, Ali Fathur (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
This research is related to the management of Arabic language skills in the Arabic Language Teaching Division, College of Education and Schooling, Mataram Islamic State University. This research aims to analyze the management of the Arabic language skill, and to define and analyze the impact of implementing the Arabic language skill management in the Arabic Language Teaching Division, College of Education and Schooling, Mataram Islamic State University. This research uses the descriptive qualitative approach. The method of collecting data is observation, interview and documentation. The observation was used to obtain information related to the activity and conditions in the Arabic Language Skills Department in the Arabic Language Teaching Division, College of Education and Schooling, Mataram State Islamic University. The interview was conducted to obtain data and information related to the management of the Arabic language skill in the Arabic Language Teaching Division, College of Education and Schooling, Mataram Islamic State University. As for the documentation method, it is used to obtain data and information related to the image of the Arabic language skill management in the Arabic Language Teaching Division, College of Education and Schooling, Mataram Islamic State University. Managing the Arabic language skill in the Arabic Language Teaching Division is done in an open manner between the president and the lecturer. As well as the application of teaching Arabic language skills, including listening, speaking, reading, and writing. And teaching students the Arabic language skill in quality management from the first to the last and from the first level to the next.